Pengembangan Instrumen Assessment IDEAL Problem Solving Pada Materi Koloid - Amaliah, Nor; Munzil, Munzil; Yahmin, Yahmin (Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Negeri Makassar, 2025)
Problem solving is one of the abilities that students must have in the 21st century. This is because students' ability to solve problems is expected to increase their higher order thinking skills (HOTS) competency. The ability to measure problem solving can be assessed through test instruments in the form of questions containing problems. This research aims to analyze problem solving abilities in colloidal materials through the development of the IDEAL Problem Solving assessment instrument. This instrument includes five indicators, namely Identify the Problem, Define the Outcome, Explore Possible Strategies, Anticipate Outcome & Act, and Look back and Learn. The research was conducted for 3 months at SMAN 1 Sungai Tabuk class XI semester II (even). The method used is development research or R&D (Research and Development) research. The development of this instrument adapts the ADDIE development model by following five steps, including (1) Analyze (analysis), (2) Design (planning), (3) Develop (development), (4) Implementation (implementation), (5) Evaluate (evaluation). Data analysis was carried out quantitatively with statistical tests. The empirical validity results show that the instrument is valid and reliable to use and meets the criteria for a good level of difficulty and discrimination.